Crystalline and Amorphous Cerium Phosphate Nanoparticles as Enzyme-Mimetic Nanomaterials for Regenerative Medicine - Ekaterina V. Silina; Artem S. Chizhov; Maria P. Kruglova; Alexey A. Kryukov; Svetlana A. Dodonova; Maksim A. Pugachevskii; Natalia E. Manturova; Victor A. Stupin (Nanomaterials, 2026)
Wounds represent a persistent challenge in modern medicine, driving the search for novel nanomaterials capable of modulating oxidative stress and promoting tissue regeneration. While cerium oxide nanoparticles have been extensively studied for their enzyme-mimetic activity, hydrated cerium orthophosphates remain relatively unexplored despite their promising biocompatibility and redox properties. The aim of the study is the synthesis of cerium phosphate nanoparticles (CePO4 NPs) via controlled hydrolysis of a Ce(NO3)3–sodium tripolyphosphate complex under different temperature regimes (60 °C (CePO4-1) and 90 °C (CePO4-2)), their physicochemical characterization (using transmission electron microscopy, X-ray diffraction, X-ray photoelectron spectroscopy, dynamic light scattering, UV spectroscopy), and the evaluation of their biocompatibility and biological activity in relation to human cells involved in skin regeneration. Their biological activity was evaluated on human dermal fibroblasts (BJ TERT) and keratinocytes (HaCaT) using MTT assays and direct cell counting across a broad concentration range (10−2–10−4 M). Synthesis temperature critically governed the atomic structure without significantly altering NPs size. CePO4-1 (4.7 ± 1.2 nm) was X-ray amorphous with a high density of oxygen vacancies and a mixed Ce3+/Ce4+ valence state on the surface (the physical basis for its antioxidant enzyme-mimetic and pro-regenerative activity); CePO4-2 (5.2 ± 0.9 nm) formed highly crystalline hexagonal rhabdophane. Both nanoparticle types demonstrated biocompatibility. A dose-dependent stimulating effect of NPs on the metabolism and proliferation of fibroblasts (by 1.14–1.45 times) was established. In contrast, keratinocytes exhibited dose-dependent metabolic suppression at higher concentrations (10−2–10−3 M), while remaining unaffected at 10−4 M. The amorphous, defect-rich CePO4-1 exhibited pronounced biological activity, significantly stimulating fibroblast metabolic (up to 128%) and proliferative (up to 145%) activity. Thus, the temperature control during the CePO4 NPs synthesis enables the “physical programming” of biological activity, presenting a promising strategy for the development of biocompatible, enzyme-mimetic and redox-mediated wound-healing nanodrugs.